2008
DOI: 10.1002/j.1551-8833.2008.tb09654.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the carbon footprint of water production

Abstract: A carbon footprint (CF) analysis is the sum of the estimated carbon dioxide and other greenhouse gas (GHG) emissions associated with a particular activity or industry. Without a standardized protocol for developing a CF of water production, U.S. utilities must draw on the experiences of other nations and adapt approaches used in other industries. In the United Kingdom, mandatory regulation of emissions for large industry has spurred collaborative development of CF methods for the water industry. British and Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…A study in Sweden evaluating water management infrastructures through LCA showed that the installation phase is primarily responsible for the greenhouse gas emissions caused by the main water supply network, even though it can be foreseen that in future scenarios the stages of maintenance and renewal would be the major contributors (Venkatesh et al 2009). The emissions associated with the construction of a single pipe were estimated to account for over 80% of the total impact during its life cycle (Strutt et al 2008). The proposed use of alternative materials including recycled steel in the production of these concrete structures can reduce emissions by 25% (Venkatesh et al 2009).…”
Section: Environmental Assessment Of Rwh At An Urban Scalementioning
confidence: 99%
“…A study in Sweden evaluating water management infrastructures through LCA showed that the installation phase is primarily responsible for the greenhouse gas emissions caused by the main water supply network, even though it can be foreseen that in future scenarios the stages of maintenance and renewal would be the major contributors (Venkatesh et al 2009). The emissions associated with the construction of a single pipe were estimated to account for over 80% of the total impact during its life cycle (Strutt et al 2008). The proposed use of alternative materials including recycled steel in the production of these concrete structures can reduce emissions by 25% (Venkatesh et al 2009).…”
Section: Environmental Assessment Of Rwh At An Urban Scalementioning
confidence: 99%
“…Embodied emissions in purchased energy 3. All indirect emissions, such as those associated with transport of purchased goods, sold products, business travels, energy activities, disposal of products etc., not included in tiers I and II (WRI/WBCSD 2004;Carbon Trust 2007a, b;BSI 2008;CDP 2008;Matthews et al 2008a, b;Strutt et al 2008). Figure 2 illustrates the three tiers in carbon footprint estimation.…”
Section: Setting Boundarymentioning
confidence: 95%
“…While CO 2 is the best studied and most known, CH 4 , which constitutes up to 75% of the total gas emitted during anaerobic wastewater treatment, is 25 times more potent as a greenhouse gas (Forster et al, 2007;Daelman et al, 2012). Similarly nitrous oxide, although emitted in relatively low amounts, is 300 times more damaging than CO 2 (Daelman et al, 2012;Strutt et al, 2008). While, harvesting and/or recycling of these gases can potentially avert any detrimental impact (Oswald, 1995;Green et al, 1995a), it is now understood that methane-oxidising bacteria (MOB), a relatively common group of bacteria capable of utilising CH 4 as their sole carbon and energy source if sufficient O 2 is present, utilise in-pond algae-derived O 2 to consume much of the emitted CH 4 before it reaches the atmosphere ( Van der Ha et al, 2011;authors' unpublished data).…”
Section: Iaps As a Global Wastewater Treatment Technologymentioning
confidence: 99%